Opiorphin is a master regulator of the hypoxic response in corporal smooth muscle cells. Issue 8 (6th May 2014) - Fu, Shibo; Tar, Moses Tarndie; Melman, Arnold; Davies, Kelvin Paul
Abstract : Men with sickle cell disease (SCD) risk developing priapism. Recognizing that SCD is a disease of hypoxia, we investigated the effect of hypoxia on gene expression in corporal smooth muscle (CSM) cells. Rat CSM cells in vitro were treated with CoCl2 or low oxygen tension to mimic hypoxia. Hypoxic conditions increased expression of genes previously associated with priapism in animal models. Variable coding sequence a1 (Vcsa1; the rat opiorphin homologue, sialorphin), hypoxia‐inducible factor 1a (Hif‐1a), and A2B adenosine receptor (a2br) were increased by 10‐, 4‐, and 6‐fold, respectively, by treatment with CoCl2, whereas low oxygen tension caused increases in expression of 3‐, 4‐, and 1.5‐fold, respectively. Sialorphin‐treated CSM cells increased expression of Hif‐1a and a2br by 4‐fold, and vcsa1‐siRNA treatment reduced expression by ~50%. Using a Hif‐1a inhibitor, we demonstrated up‐regulation of a2br by sialorphin is dependent on Hif‐1a, and knockdown of vcsa1 expression with vcsa1 ‐si RNA demonstrated that hypoxic‐upregulation of Hif‐1a is dependent on vcsa1. In CSM from a SCD mouse, there was 15‐fold up‐regulation of opiorphin at a life stage prior to priapism. We conclude that in CSM, opiorphins are master regulators of the hypoxic response. Opiorphin up‐regulation in response to SCD‐associated hypoxia activates CSM "relaxant" pathways; excessive activation of these pathways results in priapism.—Fu, S., Tar, M. T., Melman, A., Davies, K. P. Opiorphin is a master regulator of the hypoxic response in corporal smooth muscle cells. FASEB J. 28, 3633–3644 (2014). www.fasebj.org